2009
DOI: 10.1038/jcbfm.2009.24
|View full text |Cite
|
Sign up to set email alerts
|

Critical Closing Pressure: Comparison of Three Methods

Abstract: Critical closing pressure (CCP) is an arterial pressure threshold below which small arterial vessels collapse. Our aim was to compare different methods to estimate CCP in the cerebrovascular circulation using the relationships between transcranial Doppler flow velocity (FV), laser-Doppler flux (LDF), and arterial blood pressure (ABP). A total of 116 experiments in rabbits were analyzed retrospectively. At the end of each recording, cardiac arrest (CA) was induced. Arterial blood pressure in femoral artery, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 19 publications
(23 reference statements)
1
26
0
Order By: Relevance
“…This physiological phenomenon has been reported in several studies using different techniques to assess dynamic cerebral autoregulation [13,14]. Hypercapnia induces a decrease in vascular tone reflected by a decrease in cerebral arterial resistance but also in the critical closing pressure (CCP), which reflects the arterial pressure threshold below which small arterial vessels collapse [14,15,18]. This reduction in vascular tone and change in physiological properties of arterial walls may be responsible for this inability for the cerebral arteries to regulate adequately the cerebral blood flow under conditions of hypercapnia.…”
Section: Discussionmentioning
confidence: 98%
“…This physiological phenomenon has been reported in several studies using different techniques to assess dynamic cerebral autoregulation [13,14]. Hypercapnia induces a decrease in vascular tone reflected by a decrease in cerebral arterial resistance but also in the critical closing pressure (CCP), which reflects the arterial pressure threshold below which small arterial vessels collapse [14,15,18]. This reduction in vascular tone and change in physiological properties of arterial walls may be responsible for this inability for the cerebral arteries to regulate adequately the cerebral blood flow under conditions of hypercapnia.…”
Section: Discussionmentioning
confidence: 98%
“…ABP, CPP, and FV were continuously recorded, converted into digital samples using an analog-to-digital converter fitted into an IBM compatible personal computer [27] and saved on hard disk in digital form, with sampling frequency 50 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…However, investigation of CCP also has its limits, as it has recently been shown that predictions of CCP with TCD waveform analysis show substantial differences from values of CCP recorded during cardiac arrest [30], suggesting that these differences will need to be understood before indirect calculations of CCP can be reliably used in clinical practice. Since we did not investigate cerebral autoregulation, but sympathetic influence in cortical activation, we think it is also valid for intra-and interindividual comparison to use ABP/CBFV to show relative changes of cerebrovascular resistance.…”
Section: Posterior Circulationmentioning
confidence: 98%